(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The analysis shows that the number of childrenparticipating in elementary education has improved, and the improvements aremore visible among children from rural areas, educationally lagging states,girls and those from the socially and economically disadvantaged groups. Whileprivate sector capture has been increasing, government is still the majorprovider, and especially so for children from marginalized groups. At the sametime, the analysis also points to the persisting gaps in participation, completionand transition among children from the disadvantaged groups, in spite of theprogress, especially during the last decade or so. The real India live in villages’, this saying is as true today as itwas when the country got independence 65 years back. As more than half of thepopulation of the country lives in villages, rural development is an eminentfactor for the development of our economy. The crucial motivating factor forthe development of the economy in today’s time is Education.